Characteristic properties of plastic wastes: possibility of reinforcing material for soil - Yuriza, Yasmin; Tuan Ismail, Tuan Noor Hasanah; Mohamed, Ismail; Mat Hassan, Nik Normunira (2021)
The current statistic shows that the percentage of plastic has significantly increased in the landfill and leads to environmental issues due to its non-biodegradable characteristic. However, these challenges can be turned into opportunities by reusing and recycling such waste for civil engineering applications. Hence, the focuses of this paper are to analyze the possibility of utilizing plastic waste in the soil reinforcement field using VOSviewer software and to evaluate the chemical, thermal, physical and mechanical properties of the plastics (plastic straw, plastic bottle and plastic bag). The data for this study was collected from the articles published in Scopus. Nevertheless, there are very limited articles that relate soil reinforcement with thermal, chemical, physical and mechanical properties of plastic waste. Therefore, this paper aims to evaluate the properties of plastic waste, which were plastic bottle, plastic bag and plastic straw. The properties of plastic waste have been investigated to ensure it meets the requirement for soil reinforcement technology. The Fourier transform infrared (FTIR) spectra indicated the presence of carbon and hydrogen chains in those plastics waste. The plastic straw, plastic bag, and plastic bottle were degraded at 382°C, 456°C and 449°C, respectively. This finding indicated that all of these plastics waste were thermally stable in the tropical temperature. Moreover, the densities of the plastics waste were less than 1 g/cm3, which contributes to the lightweight material and it’s very crucial to eliminating the self-loading from the reinforcement material. The tensile strengths of the plastic straw and plastic bottle were 0.02 GPa and 2.22 GPa, respectively. The outstanding properties of these plastic wastes can provide manifold benefits in the geotechnical engineering application.